Anti-fog multi-layer film, laminate using same, and packaging material

JP7643647B1Active Publication Date: 2025-03-11DIC CORP
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024553203
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-06-20
Filing Date
2024-06-06
Publication Date
2025-03-11
Estimated Expiration
2044-06-06

AI Technical Summary

Benefits of technology

【0011】 本発明の多層フィルム及びこれを用いた積層体は、ポリエステル系包装容器の蓋材としてシールした際や、袋状にしてシールした際に、シール層(A)がポリエステル系包装容器やポリエステル系フィルムに強固に熱融着し、開封時には膜切れせず優れた易開封性を発現する。また防曇性が特に良好であることから、青果物や惣菜等のチルド食品等の包装材として好適に用いることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643647000001
    Figure 0007643647000001
  • Figure 0007643647000002
    Figure 0007643647000002
Patent Text Reader

Abstract

A multilayer film, laminate, packaging material, and food packaging container comprising a seal layer (A) and a resin layer (B) adjacent to the seal layer (A), the seal layer (A) containing a polyester resin (a) and an antifogging agent, and the resin layer (B) containing an acid-modified polyolefin and a polyester resin (b). It is preferable that the seal layer contains polyester resin (a1) and polyester resin (a2) as the polyester resins, the polyester resin (a1) having a glass transition temperature of 60 to 140°C, and the polyester resin (a2) having a glass transition temperature of 45°C or lower.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multilayer film that combines anti-fogging properties and easy-opening properties and that can be suitably used as a lid material for food packaging containers, and a laminate using the same. [Background technology]

[0002] Conventionally, polyester containers, which have excellent transparency and recyclability, have been widely used as packaging for refrigerated foods such as cut vegetables and cut fruits. The lids of these containers are required to have anti-fogging properties in order to improve the visibility of the contents. The reason for this is that if the inner surface of the packaging material becomes cloudy due to the evaporation of moisture from the refrigerated food in the container, the contents become difficult to see, which reduces the product value, i.e., it becomes impossible to meet the consumer demand for food safety and security. Furthermore, while it is essential for the lids of containers to have a reliable seal until the contents are removed, in the trend toward universal design, importance is placed on a method that is easy for consumers to open, such as easy opening, as a consideration for the socially vulnerable (elderly people, young children, disabled people, etc.).

[0003] Currently, known methods for imparting anti-fogging properties to packaging materials include a method in which a resin is molded into a film and then an anti-fogging agent is applied to the surface that comes into contact with the contents (see, for example, Patent Document 1), and a method in which an anti-fogging agent is kneaded into a resin used for the packaging material, which is molded into a film and then secondary molded for use in various packaging materials.

[0004] The method of applying a coating liquid containing an anti-fog agent to the surface of a film requires a step of applying the coating liquid containing the anti-fog agent and a step of drying the coating film, which results in low production efficiency. Furthermore, there is a problem that the anti-fog agent on the applied surface is washed away by evaporation of moisture from the contents, thereby reducing the durability of the anti-fog effect.

[0005] In addition, when the anti-fog agent is kneaded into the resin in a single-layer film or in all layers of a multilayer film, when the surface is printed or laminated with another base film, the anti-fog agent bleeds out on the surface and acts on the printing ink or adhesive, which may cause peeling of the printed surface or poor adhesion. On the other hand, in a method of kneading an anti-fog agent into a sealing layer (A) of a multilayer film (see, for example, Patent Document 2), the anti-fog agent has a property of being easily mobile in the multilayer film, so that the anti-fog effect is not constant and there is concern about the durability of the effect. In addition, the anti-fog agent migrates to a layer adjacent to the layer containing the anti-fog agent, which may reduce the adhesion between the layers and cause deterioration of the film cutability.

[0006] In response to these problems, the applicants conducted research and discovered that a film having an anti-fogging agent in a heat seal layer and having an adjusted free volume pore size and rigidity in the heat seal layer can suppress deterioration of film tearability over time, and thus completed the invention of Patent Document 3. The present invention has been developed in order to achieve both better film tearability and anti-fogging properties, and to improve seal strength. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2004-025825 A [Patent Document 2] JP 2019-171792 A [Patent Document 3] WO2023 / 063091 publication Summary of the Invention [Problem to be solved by the invention]

[0008] In view of the above circumstances, an object of the present invention is to provide a multilayer film which has good film tearability and excellent easy-open properties, is particularly excellent in anti-fogging properties that prevent fogging due to water vapor from the contents, and has good seal strength, and is suitable for use as a lid material for packaging containers, etc., a laminate obtained by laminating this multilayer film onto a base film, and a packaging material using the same. [Means for solving the problem]

[0009] As a result of intensive research into solving the above problems, the present inventors have found that the above problems can be solved by a multilayer film comprising a sealing layer (A) and a resin layer (B) adjacent to the sealing layer (A), wherein the sealing layer (A) contains a polyester-based resin (a) and an anti-fogging agent, and the resin layer (B) contains an acid-modified polyolefin and a polyester-based resin (b), and have completed the present invention.

[0010] That is, the present invention provides a multilayer film, a packaging material, and a food packaging container as set forth in (1) to (10) below. (1) A seal layer (A) and a resin layer (B) adjacent to the seal layer (A), the sealing layer (A) contains a polyester-based resin (a) and an antifogging agent, The resin layer (B) contains an acid-modified polyolefin and a polyester-based resin (b). Multilayer film. (2) The sealing layer contains a polyester-based resin (a1) and a polyester-based resin (a2) as polyester-based resins, The multilayer film according to (1), wherein the polyester resin (a1) has a glass transition temperature of 60 to 140° C., and the polyester resin (a2) has a glass transition temperature of 45° C. or lower. (3) The multilayer film according to (1), wherein the glass transition temperature of the polyester resin (b) is 45° C. or lower. (4) The multilayer film according to (1), wherein the amount of the antifogging agent in the sealing layer (A) is 1.0 to 7.0% by mass. (5) The multilayer film according to (1), wherein the mass ratio of the acid-modified polyolefin to the polyester resin (b) in the resin layer (B) is 45:55 to 95:5. (6) The multilayer film according to (1), further comprising a laminate layer (A). (7) A laminate having the multilayer film according to any one of (1) to (6). (8) A packaging material using the laminate described in (7). (9) The packaging material according to (8), which is a lid material for a food packaging container. (10) A food packaging container using the packaging material described in (9) as a lid material, characterized in that the portion of the food packaging container that is bonded to the lid material contains a polyester-based resin. Effect of the Invention

[0011] The multilayer film and the laminate using the same of the present invention, when used as a lid material for a polyester-based packaging container or when sealed in a bag shape, exhibit excellent ease of opening without film tearing when opened, since the sealing layer (A) is strongly heat-sealed to the polyester-based packaging container or polyester-based film. In addition, since the anti-fogging property is particularly good, the laminate can be suitably used as a packaging material for chilled foods such as fruits and vegetables and prepared foods. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The multilayer film of the present invention and each of the components constituting the laminate using the same will be described in detail below.

[0013] <Sealing layer (A)> In the multilayer film of the present invention, the sealing layer (A) contains a polyester resin (a) and an antifogging agent. The sealing layer (A) constitutes the surface layer on one side of the multilayer film and laminate of the present invention, and is a layer that seals the sealing surface of a polyester-based packaging container. It also has an anti-fogging function and can turn water droplets attached to the surface of the multilayer film and laminate on the inside side of the container into a water film, thereby reducing fogging caused by water vapor of the contents and improving the visibility of the contents.

[0014] <Anti-fogging agent> The sealing layer (A) used in the present invention contains an antifogging agent. The antifogging agent is not particularly limited as long as it is generally known to impart antifogging properties, and examples of the antifogging agent that can be used include anionic surfactants, nonionic surfactants, cationic surfactants, amphoteric surfactants, etc. Among these, it is preferable to use nonionic surfactants.

[0015] Specific examples of the nonionic surfactant include sorbitan surfactants such as sorbitan monostearate, sorbitan distearate, sorbitan monopalmitate, sorbitan dipalmitate, sorbitan monobehenate, sorbitan dibehenate, sorbitan monolaurate, and sorbitan dilaurate; glycerin surfactants such as glycerin monolaurate, glycerin dilaurate, diglycerin monopalmitate, diglycerin dipalmitate, glycerin monostearate, glycerin distearate, diglycerin monostearate, diglycerin distearate, diglycerin monolaurate, and diglycerin dilaurate; polyethylene glycol monostearate, polyethylene glycol dilau ... Examples of such surfactants include polyethylene glycol surfactants such as polyethylene glycol monopalmitate; trimethylolpropane surfactants such as trimethylolpropane monostearate; diethanol alkylamine and diethanol alkylamide surfactants such as lauryl diethanolamine, oleyl diethanolamine, stearyl diethanolamine, lauryl diethanolamide, oleyl diethanolamide, and stearyl diethanolamide; pentaerythritol surfactants such as pentaerythritol monopalmitate, and polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan distearate, and mono- and distearates of sorbitan-diglycerin condensates. These surfactants may be used alone or in combination of two or more. Glycerin surfactants are particularly preferred.

[0016] The lower limit of the proportion of the antifogging agent in the seal layer (A) used in the present invention is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, based on the total mass of the layer. By using the antifogging agent in this range, the antifogging property is easily exhibited. The upper limit of the proportion is preferably 7.0% by mass or less, more preferably 5.0% by mass or less, and even more preferably 4.0% by mass or less, based on the total mass of the seal layer (A). By using the antifogging agent in this range, excessive migration of the antifogging agent to the layer in contact with the seal layer (A) is unlikely to occur, and the decrease in interlayer strength can be suppressed. That is, the amount of the antifogging agent in the seal layer (A) is preferably 0.5 to 7.0% by mass, more preferably 1.0 to 7.0% by mass, even more preferably 1.0 to 5.0% by mass, and particularly preferably 1.0 to 4.0% by mass.

[0017] <Polyester resin (a)> The sealing layer (A) used in the present invention contains a polyester resin (a). The polyester resin (a) contains, as a polyvalent carboxylic acid component, a component selected from phthalic acid, terephthalic acid, isophthalic acid, orthophthalic acid, adipic acid, sebacic acid, naphthalenedicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-phenylenedioxydiacetic acid, and structural isomers thereof, dicarboxylic acids such as malonic acid, succinic acid, and adipic acid, or derivatives thereof, p-hydroxybenzoic acid, p-hydroxybenzoic acid esters, and oxyacids such as glycolic acid, or derivatives thereof, and a polyhydric alcohol component selected from ethylene glycol, diethylene glycol, propylene glycol, 2-methyl-1,3-propanediol, 2,2-dimethyltrimethylene glycol, 1,4-butanediol, 1,5-pentanediol, 3-methylpentanediol, 1,6-hexanediol, and the like. The dibasic acid component and the glycol component are reacted with one or more of the following components to carry out an ester exchange reaction or esterification reaction, followed by a melt polycondensation reaction.

[0018] From the viewpoint of exhibiting sealing properties with polyester-based packaging containers, the sealing layer (A) used in the present invention preferably contains the above-mentioned polyester-based resin (a) in an amount of 90 mass% or more based on the total amount of resin components forming the sealing layer (A).

[0019] The polyester resin (a) may be used alone or in combination. Among them, it is preferable to use, as the polyester resin (a), a polyester resin (a1) having a glass transition temperature of 60 to 140° C. and a polyester resin (a2) having a glass transition temperature of 45° C. or less in combination. By using the polyester resin (a1) and the polyester resin (a2) in combination, the function of the antifogging agent is easily exhibited, and it is easy to achieve compatibility with the seal strength. The glass transition temperature (Tg) of the polyester resin (a) is a value determined by a method conforming to Japanese Industrial Standards (JIS K7121), that is, by differential scanning calorimetry (DSC) method.

[0020] (Polyester resin (a1)) The polyester resin (a1) is a polyester resin (a) having a glass transition temperature of 60 to 140° C. The polyester resin (a1) is obtained by polycondensation of a polyvalent carboxylic acid and a polyhydric alcohol.

[0021] Examples of the polyvalent carboxylic acid include malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, hexahydrophthalic acid, 1,4-cyclohexanedicarboxylic acid, maleic acid, maleic anhydride, citraconic acid, dimethylmaleic acid, cyclopentene-1,2-dicarboxylic acid, 1-cyclohexene-1,2-dicarboxylic acid, 4-cyclohexene-1,2-dicarboxylic acid, fumaric acid, mesaconic acid, itaconic acid, glutaconic acid, phthalic acid, phthalic anhydride, terephthalic acid, isophthalic acid, orthophthalic acid, 1,2,5-hexanetricarboxylic acid, 1,2,4-cyclohexanetricarboxylic acid, trimellitic acid, trimellitic anhydride, 1,2,5-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, pyromellitic acid, pyromellitic anhydride, etc. These may be used alone or in combination of two or more. Furthermore, as required, monocarboxylic acids such as methanoic acid, ethanoic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, heptadecanoic acid, and octadecanoic acid may be used as the raw material components.

[0022] Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, propylene glycol, 2-methyl-1,3-propanediol, 2,2-dimethyltrimethylene glycol, 1,4-butanediol, 1,5-pentanediol, 3-methylpentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, 1,20-icosanediol, 1,4-cyclohexanedimethanol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene ether glycol, neopentyl glycol, pentaethylene glycol, isosorbide, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and trimethylolpropane. These may be used alone or in combination of two or more kinds. Among them,

[0023] The polyvalent carboxylic acid and the polyhydric alcohol may be used in any combination.Specific examples include terephthalic acid / ethylene glycol / neopentyl glycol copolymer, terephthalic acid / ethylene glycol / 1,4-cyclohexanedimethanol / isosorbide copolymer, terephthalic acid / isophthalic acid / ethylene glycol copolymer, terephthalic acid / ethylene glycol / 1,4-cyclohexanedimethanol copolymer, and terephthalic acid / 1,4-cyclohexanedimethanol / 2,2,4,4-tetramethyl-1,3-cyclobutanediol copolymer.

[0024] The glass transition temperature of the polyester resin (a1) is 60 to 140° C., preferably 60 to 130° C., and more preferably 60 to 120° C. By using the polyester resin (a1) having such a glass transition temperature, suitable film processability and heat resistance can be ensured. Examples of such polyester resins (a1) include, but are not limited to, resins commercially available under the trade name "ECOZEN" (SK Chemicals).

[0025] (Polyester resin (a2)) The polyester resin (a2) is a polyester resin (a) having a glass transition temperature of not more than 45° C. The polyester resin (a2) is obtained by polycondensation of a polyvalent carboxylic acid and a polyhydric alcohol.

[0026] Examples of the polycarboxylic acid include aromatic polycarboxylic acids such as phthalic acid, phthalic anhydride, terephthalic acid, isophthalic acid, orthophthalic acid, naphthalenedicarboxylic acid, and trimellitic acid, and aliphatic polycarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, decanoic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, heptadecanedioic acid, hexadecanedioic acid, heptadecanedioic acid, octadecanedioic acid, dimer acid, and cyclohexanedicarboxylic acid. These may be used alone or in combination of two or more kinds. Furthermore, as required, monocarboxylic acids such as methanoic acid, ethanoic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, heptadecanoic acid, and octadecanoic acid may be used as the raw material components.

[0027] Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, propylene glycol, 2-methyl-1,3-propanediol, 2,2-dimethyltrimethylene glycol, 1,4-butanediol, 1,5-pentanediol, 3-methylpentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, 1,20-icosanediol, 1,4-cyclohexanedimethanol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene ether glycol, neopentyl glycol, pentaethylene glycol, and trimethylolpropane. These may be used alone or in combination of two or more.

[0028] The polyvalent carboxylic acid and the polyhydric alcohol may be used in any combination.Specific examples of the polyvalent carboxylic acid and the polyhydric alcohol include terephthalic acid / ethylene glycol copolymer, terephthalic acid / 1,4-butanediol copolymer, terephthalic acid / adipic acid / 1,4-butanediol copolymer, terephthalic acid / polytetramethylene ether glycol / 1,4-butanediol copolymer, terephthalic acid / isophthalic acid / 1,4-butanediol / polytetramethylene ether glycol copolymer, terephthalic acid / isophthalic acid / 1,4-butanediol copolymer, and terephthalic acid / isophthalic acid / 1,4-butanediol / polytetramethylene ether glycol / 1,4-butanediol copolymer.

[0029] The glass transition temperature of the polyester resin (a2) is 45° C. or lower, preferably −80 to 40° C., more preferably −80 to 0° C., and even more preferably −80 to −20° C. By using a polyester resin (a2) having such a glass transition temperature, the function of the antifogging agent is easily exhibited, and it becomes easy to balance this with the seal strength. Examples of such polyester resins (a2) include, but are not limited to, resins commercially available under the trade name "Vylon" (Toyobo Co., Ltd.).

[0030] In the seal layer (A) of the present invention, when a polyester resin (a1) having a glass transition temperature of 60 to 140°C and a polyester resin (a2) having a glass transition temperature of 45°C or less are used in combination as the polyester resin (a), the total content of the polyester resin (a1) and the polyester resin (a2) in the seal layer (A) is preferably 70% by mass or more in terms of obtaining suitable heat sealability and heat resistance. In addition, in terms of obtaining a suitable film appearance, it is more preferably 75% by mass or more, and more preferably 80% by mass or more. The upper limit of the content is not particularly limited, but is preferably 99% by mass or less, and more preferably 97% by mass or less.

[0031] The content of the polyester resin (a1) in the seal layer of the present invention is preferably 20 to 90% by mass, more preferably 30 to 80% by mass, and even more preferably 50 to 70% by mass. The content of the polyester resin (a2) in the seal layer of the present invention is preferably 10 to 80% by mass, more preferably 20 to 70% by mass, and even more preferably 30 to 50% by mass. When the content is within this range, it is preferable because both antifogging properties and heat sealability can be achieved.

[0032] The content ratio of the polyester resin (a1) to the polyester resin (a2) is preferably 20:80 to 90:10, more preferably 30:70 to 80:20, and even more preferably 50:50 to 70:30. When the content ratio is within this range, the function of the antifogging agent is easily exhibited, and both antifogging properties and film cuttability can be achieved, and transparency is also good.

[0033] The polyester resin (a) in the sealing layer (A) used in the present invention may be a biodegradable polyester. Examples of biodegradable polyesters include polyhydroxyalkanoates such as polylactic acid resins, poly(butylene succinate) (PBS), poly(butylene succinate / adipate) copolymers (PBSA), poly(3-hydroxybutyric acid), copolymers of 3-hydroxybutyric acid and 3-hydroxyvaleric acid, and copolymers of 3-hydroxybutyric acid and 4-hydroxybutyric acid; aliphatic polyester compounds such as polyglycolic acid, polycaprolactone, ring-opening polymers such as β-propiolactone and γ-valerolactone; polyesters composed of aliphatic dibasic acids and aliphatic diols, such as copolyesters of adipic acid, 1,4-butanediol, and terephthalic acid (polybutylene adipate terephthalate), and polyesters composed of succinic acid and ethylene glycol (polyethylene succinate); copolymers of aromatic polyesters and aliphatic polyesters; and copolymers of aliphatic polyesters and polyamides. In addition, the composition may further contain other biodegradable resins such as polyvinyl alcohol, pullulan, chitosan, curdlan, starch-based green plastic, esterified starch, cellulose, and cellulose acetate.

[0034] The resin constituting the sealing layer (A) in the present invention may be used in combination with other resins as long as the sealing property and anti-fogging property are not impaired. From the viewpoint of exhibiting the sealing property with the polyester-based packaging container, the content of the other resin in the sealing layer (A) is preferably 10% by mass or less, more preferably 5% by mass or less, and more preferably completely absent, based on the total amount of the resin components constituting the sealing layer (A).

[0035] Examples of the other resins include polyolefin resins such as ethylene resins, propylene resins, and cyclic olefin resins; thermoplastic elastomers such as polyethylene elastomers, polypropylene elastomers, and butene elastomers; ethylene copolymers such as ethylene-vinyl acetate copolymer (EVA), ethylene-methyl methacrylate copolymer (EMMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl acrylate (EMA) copolymer, ethylene-ethyl acrylate-maleic anhydride copolymer (E-EA-MAH), ethylene-acrylic acid copolymer (EAA), and ethylene-methacrylic acid copolymer (EMAA); and further ionomers of ethylene-acrylic acid copolymers, ionomers of ethylene-methacrylic acid copolymers, and other biodegradable resins mentioned above. Examples of ethylene resins include polyethylene resins such as very low density polyethylene (VLDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), linear medium density polyethylene (LMDPE), medium density polyethylene (MDPE), and high density polyethylene (HDPE). Examples of propylene resins include propylene homopolymers, propylene-α-olefin random copolymers such as propylene-ethylene butene-1 copolymers, and propylene block copolymers such as propylene-α-olefin block copolymers. Examples of cyclic olefin resins include norbornene polymers, vinyl alicyclic hydrocarbon polymers, and cyclic conjugated diene polymers. Among these, norbornene polymers are preferred. Examples of norbornene polymers include ring-opening polymers of norbornene monomers (hereinafter sometimes referred to as "COP"), norbornene copolymers obtained by copolymerizing norbornene monomers with olefins such as ethylene (hereinafter sometimes referred to as "COC"), and the like.

[0036] The sealing layer (A) used in the present invention may contain components such as antistatic agents, heat stabilizers, nucleating agents, antioxidants, lubricants, antiblocking agents, mold release agents, UV absorbers, colorants, and biodegradable agents, as long as the objects of the present invention are not impaired. In particular, in order to provide the processing suitability during multilayer film molding and the packaging suitability of the filling machine, it is preferable that the friction coefficient of the multilayer film surface is 2.0 or less, and in particular 1.5 or less, so that it is preferable to appropriately add lubricants, antiblocking agents, and antistatic agents to the sealing layer (A) that becomes the surface layer of the multilayer film of the present invention. Additives such as lubricants and antiblocking agents are not particularly limited, and commercially available ones can be used.

[0037] <Resin layer (B)> The resin layer (B) of the present invention is a layer adjacent to the sealing layer (A) and contains an acid-modified polyolefin and a polyester-based resin (b).

[0038] <Acid-modified polyolefin> The resin layer (B) of the present invention contains an acid-modified polyolefin. The olefin component constituting the main chain of the acid-modified polyolefin is not particularly limited, but is preferably an alkene having 2 to 6 carbon atoms such as ethylene, propylene, isobutylene, 2-butene, 1-butene, 1-pentene, 1-hexene, etc., and a mixture thereof may be used. Among these, an alkene having 2 to 4 carbon atoms such as ethylene, propylene, isobutylene, 1-butene, etc. is more preferred, ethylene and propylene are even more preferred, and ethylene is most preferred.

[0039] The acid-modified polyolefin contains a (meth)acrylic acid ester component. Examples of the (meth)acrylic acid ester component include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, and stearyl (meth)acrylate. From the viewpoint of availability and adhesiveness, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and hexyl acrylate are more preferred, and methyl acrylate and ethyl acrylate are more preferred. The (meth)acrylic acid ester component may be copolymerized with the olefin component, and the form is not limited. Examples of the copolymerization state include random copolymerization, block copolymerization, and graft copolymerization (graft modification). (Note that "(meth)acrylic acid" means "acrylic acid or methacrylic acid.") Specific examples of ethylene-(meth)acrylic acid ester copolymers include Elbaloy (product name: manufactured by DuPont-Mitsui Polychemicals Co., Ltd.) and Acryft (product name: manufactured by Sumitomo Chemical Co., Ltd.). These may be used alone or in combination of two or more.

[0040] The acid-modified polyolefin may be modified with an unsaturated carboxylic acid component. Examples of the unsaturated carboxylic acid component include acrylic acid, methacrylic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, crotonic acid, and the like, as well as half esters and half amides of unsaturated dicarboxylic acids. Among them, acrylic acid, methacrylic acid, maleic acid, and maleic anhydride are preferred, and acrylic acid and maleic anhydride are particularly preferred. The unsaturated carboxylic acid component may be copolymerized with the olefin component, and the form is not limited thereto. Examples of the copolymerization state include random copolymerization, block copolymerization, and graft copolymerization (graft modification). Specifically, for example, an ethylene-acrylic acid copolymer may be Nucrel (trade name: manufactured by DuPont-Mitsui Polychemicals Co., Ltd.). An ethylene-(meth)acrylic acid ester-maleic anhydride copolymer may be Bondine (trade name: manufactured by Arkema Co., Ltd.). These may be used alone or in combination of two or more.

[0041] The acid-modified polyolefin preferably has an acid modification rate of 0.5 to 40%, more preferably 0.5 to 35%, and particularly preferably 0.5 to 30%, from the viewpoint of good adhesiveness.

[0042] The resin layer (B) in the present invention preferably contains the acid-modified polyolefin in an amount of 40 to 95 mass %, more preferably 51 to 95 mass %, and even more preferably 55 to 90 mass %. By controlling the content of the acid-modified polyolefin within this range, sufficient interlayer strength between the seal layer (A) and the resin layer (B) can be obtained.

[0043] <Polyester resin (b)> In the resin layer (B) of the present invention, a polyester-based resin (b) is used in combination with the acid-modified polyolefin. By using the acid-modified polyolefin in combination with the polyester-based resin (b), the interlayer strength between the seal layer (A) containing the antifogging agent and the resin layer (B) is greatly improved without deteriorating the transparency, and the film tearability is improved. In general, acid-modified polyolefins are known as adhesive resins and have been used to bond different resin layers (e.g., polyester resin layers and polyolefin resin layers). Therefore, it has been thought that the interlayer adhesion is reduced when another resin is used in combination with acid-modified polyolefins. However, in the present invention, it has been found that the above-mentioned resin layer (B) has an effect of suppressing adhesion inhibition caused by anti-fog components, particularly in the interlayer adhesion between a polyester seal layer containing an anti-fog agent and a different resin layer.

[0044] The polyester resin (b) may be the same as the polyester resin (a) described above, but it is particularly preferable to use a polyester resin (b) having a glass transition temperature of 45° C. or less, and the same as the polyester resin (a2) described above may be used. By using a polyester resin (b) having a glass transition temperature of 45° C. or less, the interlayer adhesion is good even in the presence of an antifogging agent, and as a result, the amount of the antifogging agent in the sealing layer can be increased, leading to improved antifogging properties. Biodegradable polyesters may also be used. The polyester resin (b) is particularly preferably a polyester resin (b) obtained by polycondensation of a low-molecular-weight polyhydric alcohol having a molecular weight of 2000 or less and a polycarboxylic acid. The glass transition temperature of the polyester resin (b) is preferably 45°C or lower, more preferably from -80 to 40°C, further preferably from -80 to 0°C, and particularly preferably from -80 to -20°C.

[0045] The content of the polyester resin (b) in the resin layer (B) of the present invention is preferably from 5 to 60% by mass, more preferably from 5 to 49% by mass, and further preferably from 10 to 45% by mass.

[0046] The mass ratio of the acid-modified polyolefin to the polyester resin (b) in the resin layer (B) of the present invention is preferably 30:70 to 95:5, more preferably 40:60 to 95:5, and even more preferably 45:55 to 95:5. When the mass ratio is within this range, the interlayer strength is improved, and thus the film tearability is easily improved.

[0047] Components such as antistatic agents, heat stabilizers, nucleating agents, antioxidants, lubricants, antiblocking agents, release agents, ultraviolet absorbers, colorants, and biodegradable agents may also be added to the resin layer (B) as long as the object of the present invention is not impaired.

[0048] (Other layers) The multilayer film of the present invention may contain layers other than the seal layer (A) and the resin layer (B). The other layers may be polyester-based resin layers, polyolefin-based resin layers, etc., but are not particularly limited thereto. It is also preferable that the other layers contain two or more polyolefin resin layers. In this case, the layer constituting the other surface of the multilayer film of the present invention other than the seal layer (A) is referred to as the "laminate layer", and the layer located between the laminate layer and the resin layer (B) is referred to as the "intermediate layer".

[0049] (Polyolefin resin layer) The multilayer film of the present invention preferably contains two or more polyolefin resin layers in addition to the above-mentioned sealing layer (A) and resin layer (B).

[0050] Examples of the polyolefin resin include, but are not limited to, ethylene resin, propylene resin, cyclic olefin resin, etc. The resin that is the main component of each layer may be appropriately selected according to the properties required for each layer of the multilayer film.

[0051] Examples of the ethylene resin include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), etc., which may be used alone or in combination. Among them, linear low-density polyethylene is preferred.

[0052] The low density polyethylene (LDPE) is 0.935g / cm 3 By "ethylene" is meant a homopolymer of ethylene having a density less than 1000 MPa.

[0053] The linear low-density polyethylene is produced by copolymerizing ethylene monomer as the main component with α-olefins such as butene-1, hexene-1, octene-1, and 4-methylpentene as comonomers by low-pressure radical polymerization using a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst, and has a density of 0.925 g / cm. 3 It refers to linear low-density polyethylene having a comonomer content of less than 0.5% by mole, and therefore is distinguished from low-density polyethylene (LDPE), which is a homopolymer of ethylene. The comonomer content in linear low-density polyethylene is preferably in the range of 0.5 to 20% by mole, and more preferably in the range of 1 to 18% by mole. In addition, when butene-1 is used as the comonomer, transparency, impact resistance, tearability, etc. are improved, and in this case, the butene monomer content is most preferably in the range of 1 to 5% by mole.

[0054] Examples of the single-site catalyst include various single-site catalysts such as metallocene catalyst systems, such as combinations of metallocene compounds of transition metals of Group IV or V of the periodic table with organoaluminum compounds and / or ionic compounds. In addition, single-site catalysts have uniform active sites, and therefore, compared with multi-site catalysts, which have non-uniform active sites, the molecular weight distribution of the resulting resin is sharper, and therefore, when formed into a film, there is less precipitation of low molecular weight components, and a resin with excellent physical properties such as stable seal strength and excellent blocking resistance is obtained, which is preferable.

[0055] The above medium density polyethylene (MDPE) is 0.925g / cm 3 More than 0.942g / cm 3 It means a copolymer of ethylene and α-olefin having a density of less than 10 ...

[0056] The above high density polyethylene (HDPE) is 0.942g / cm 3 It may be a homopolymer of ethylene or a copolymer of ethylene and an α-olefin, but since an increase in the amount of the α-olefin serving as a comonomer reduces the density, it is preferable to have a small amount of comonomer, and specifically, the comonomer ratio is preferably 0.5% or less.

[0057] In commercially available products, the comonomer ratio may not be disclosed, so linear low-density polyethylene, medium-density polyethylene, and high-density polyethylene are distinguished by density, and low-density polyethylene and medium-density polyethylene are distinguished by whether they are homopolymers of ethylene or not. In the present invention, even if a product is commercially available as linear low-density polyethylene, a product having a density of 0.925 g / cm3 may be used. 3 The above can be treated as medium density polyethylene. For example, the density is 0.926 g / cm 3 If there is a polyethylene of this type, if it is an ethylene homopolymer it should be treated as low density polyethylene, and if it is an ethylene and α-olefin copolymer it should be treated as medium density polyethylene.

[0058] As the ethylene-based resin, biomass-derived polyethylene may be used, for example, biomass-derived low-density polyethylene (product name: SBC818, density: 0.918 g / cm) manufactured by Braskem. 3 , MFR: 8.1 g / 10 min), and biomass-derived low-density polyethylene manufactured by Braskem (product name: SPB681, density: 0.922 g / cm 3, MFR: 3.8g / 10min), and Braskem biomass-derived linear low-density polyethylene (product name: SLL118, density: 0.916g / cm 3 , MFR: 1.0 g / 10 min.)

[0059] Furthermore, the ethylene-based resin may be mixed with an ethylene-based copolymer such as ethylene-vinyl acetate copolymer (EVA), ethylene-methyl methacrylate copolymer (EMMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl acrylate (EMA) copolymer, ethylene-ethyl acrylate-maleic anhydride copolymer (E-EA-MAH), ethylene-acrylic acid copolymer (EAA), or ethylene-methacrylic acid copolymer (EMAA); or further with an ionomer of an ethylene-acrylic acid copolymer, or an ionomer of an ethylene-methacrylic acid copolymer.

[0060] Examples of the propylene-based resin include propylene homopolymer, propylene-ethylene copolymer, propylene-butene-1 copolymer, propylene-ethylene-butene-1 copolymer, metallocene catalyst-based polypropylene, etc. These may be used alone or in combination. In particular, it is preferable to use a propylene-based copolymer as the polypropylene-based resin, since it is easy to obtain a seal strength. When the polypropylene-based resin is used in the seal layer used in the present invention, the heat resistance of the film is improved and the heat seal strength can be increased, so that it can be suitably used as a packaging material for heavy goods.

[0061] Examples of the cyclic olefin resin include norbornene polymers, vinyl alicyclic hydrocarbon polymers, and cyclic conjugated diene polymers. Among these, norbornene polymers are preferred. Examples of norbornene polymers include ring-opening polymers of norbornene monomers (hereinafter sometimes referred to as "COP") and norbornene copolymers (hereinafter sometimes referred to as "COC") obtained by copolymerizing norbornene monomers with olefins such as ethylene. Hydrogenated products of COP and COC are particularly preferred. The weight-average molecular weight of the cyclic olefin resin is preferably 5,000 to 500,000, more preferably 7,000 to 300,000.

[0062] The norbornene monomers used as raw materials for the norbornene polymers are alicyclic monomers having a norbornene ring. Examples of such norbornene monomers include norbornene, tetracyclododecene, ethylidenenorbornene, vinylnorbornene, ethylidetetracyclododecene, dicyclopentadiene, dimethanotetrahydrofluorene, phenylnorbornene, methoxycarbonylnorbornene, and methoxycarbonyltetracyclododecene. These norbornene monomers may be used alone or in combination of two or more.

[0063] The norbornene copolymer (COC) is a copolymer of the norbornene monomer and a copolymerizable olefin, and examples of such olefins include olefins having 2 to 20 carbon atoms such as ethylene, propylene, and 1-butene; cycloolefins such as cyclobutene, cyclopentene, and cyclohexene; and non-conjugated dienes such as 1,4-hexadiene. These olefins can be used alone or in combination of two or more.

[0064] The content of the norbornene monomer in the norbornene copolymer (COC) is preferably 40 to 90 mol %, more preferably 50 to 80 mol %. When the content is in this range, the rigidity, tearability, and processing stability of the film are improved.

[0065] Commercially available products that can be used as the cyclic olefin resin include, for example, "ZEONOR" manufactured by Zeon Corporation as a ring-opening polymer (COP) of a norbornene monomer, and "APEL" manufactured by Mitsui Chemicals, Inc. and "TOPAS" manufactured by TICONA as a norbornene copolymer (COC).

[0066] (Laminate layer) The multilayer film of the present invention preferably includes a laminate layer. The laminate layer is a layer mainly composed of a polyolefin resin, and as described above, is a layer that constitutes the other surface layer of the multilayer film of the present invention other than the seal layer (A). Also, when laminating with another substrate to form a laminate, it is a layer that is bonded to the other substrate.

[0067] Examples of the polyolefin resin that is the main component of the laminate layer include the above-mentioned ethylene resin and propylene resin. From the viewpoint of preventing peeling between the layer and the base film, the polyolefin resin has a density of 0.880 to 0.960 g / cm. 3 The following ethylene-based resins and propylene-α-olefin random copolymers polymerized using a single-site catalyst are preferred, with ethylene-based resins being particularly preferred, and linear low-density polyethylene being even more preferred.

[0068] As described above, the density of the ethylene resin is 0.880 to 0.960 g / cm 3 It is preferable that the density is 0.890 to 0.940 g / cm 3 More preferably, it is 0.890 to 0.935 g / cm 3It is more preferable that the density is within this range. If the density is within this range, the resin has a suitable rigidity, has excellent mechanical strength such as pinhole resistance, and improves film formability and extrusion suitability. In addition, the melting point is generally preferably within the range of 60 to 140°C, more preferably 70 to 135°C, and even more preferably 90 to 130°C. If the melting point is within this range, processing stability (dead hold property) and co-extrusion processability are improved. In addition, the MFR (190°C, 21.18N) of the ethylene resin is preferably 0.5 to 50g / 10 minutes, more preferably 1 to 30g / 10 minutes, even more preferably 2 to 20g / 10 minutes, and particularly preferably 5 to 15g / 10 minutes. It is preferable that the MFR is within this range in that good film formability can be obtained. By using such an ethylene-based resin, transparency can be maintained when laminated, and since it has flexibility, pinhole resistance is also good.

[0069] The propylene-based resin in the laminate layer preferably has an MFR (230° C.) of 0.5 to 30.0 g / 10 min and a melting point of 110 to 165° C., and more preferably has an MFR (230° C.) of 2.0 to 15.0 g / 10 min and a melting point of 115 to 162° C. If the MFR and melting point are within these ranges, the film formability is improved.

[0070] The density of the propylene-based resin is not particularly limited and can be appropriately selected depending on the purpose. 3 ~0.93g / cm 3 is preferred, and 0.90 g / cm 3 ~0.92g / cm 3 is more preferred.

[0071] The melting point of the propylene-based resin is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 110°C to 170°C, more preferably 121°C to 166°C, and even more preferably 121°C to 140°C.

[0072] As described above, the laminate layer is mainly composed of a polyolefin resin, but from the viewpoint of improving adhesion with adhesives or printing inks when laminating with other substrates using an adhesive or when printing, resins other than polyolefin resins may be used in combination. Examples of resins other than polyolefin resins that can be used in combination include ethylene copolymers such as ethylene-vinyl acetate copolymer (EVA), ethylene-methyl methacrylate copolymer (EMMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl acrylate (EMA) copolymer, ethylene-ethyl acrylate-maleic anhydride copolymer (E-EA-MAH), ethylene-acrylic acid copolymer (EAA), and ethylene-methacrylic acid copolymer (EMAA); and further, ionomers of ethylene-acrylic acid copolymers, ionomers of ethylene-methacrylic acid copolymers, and copolymers of monomers having a cyclic olefin structure such as norbornene monomers and ethylene, etc., which may be used alone or in combination of two or more.

[0073] The laminate layer may contain components such as antifogging agents, antistatic agents, heat stabilizers, nucleating agents, antioxidants, lubricants, antiblocking agents, release agents, UV absorbers, colorants, and biodegradable agents, as long as the object of the present invention is not impaired. In particular, in order to provide the film molding processability and the filling machine packaging suitability, the friction coefficient of the multilayer film surface is preferably 2.0 or less, and more preferably 1.5 or less, so that the laminate layer corresponding to the surface layer of the multilayer film is preferably appropriately added with lubricants, antiblocking agents, and antistatic agents. The additives such as lubricants and antiblocking agents are not particularly limited, and commercially available ones can be used. In addition, the antifogging agents described in detail in the sealing layer (A) can be used as the antifogging agents.

[0074] (Middle class) The multilayer film of the present invention may include an intermediate layer. The intermediate layer is a layer mainly composed of a polyolefin resin, and is located between the laminate layer and the resin layer (B) used in the present invention, as described above. The polyolefin resin mainly composed of the intermediate layer may be the same polyolefin resin as the polyolefin resin mainly composed of the laminate layer, and the preferred polyolefin resins are also the same. The polyolefin resin used in the intermediate layer and the polyolefin resin used in the laminate layer may be the same or different, but it is preferable to use a combination of polyolefin resins of the same system from the viewpoint of preventing peeling between the layers. When combining polyolefin resins of the same system, the densities may be the same or different.

[0075] The proportion of the polyolefin resin in the intermediate layer is preferably 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 90% by mass or more. Other resins that can be used in combination are the same as those exemplified as the resins that can be used in combination in the laminate layer.

[0076] The intermediate layer may not be present in the multilayer film of the present invention, and may be a single layer or two or more layers.

[0077] The intermediate layer may also contain components such as antistatic agents, heat stabilizers, nucleating agents, antioxidants, lubricants, antiblocking agents, release agents, ultraviolet absorbers, colorants, and biodegradable agents, as long as the objects of the present invention are not impaired. The intermediate layer may also contain an antifogging agent. When the intermediate layer contains an antifogging agent, the seal strength may decrease due to migration of the antifogging agent between the layers, but such a problem is unlikely to occur in the multilayer film of the present invention.

[0078] <Multilayer film> The multilayer film of the present invention is a multilayer film including a seal layer (A) and a resin layer (B) adjacent to the seal layer (A). The layer structure may be, for example, (1) (laminate layer) / (middle layer) / (resin layer (B)) / (seal layer (A)) (2) (Laminate layer) / (Resin layer (B)) / (Seal layer (A)) (3) (Laminate layer) / (Intermediate layer) / (Intermediate layer) / (Resin layer (B)) / (Seal layer (A)) These are shown as examples of specific embodiments of the present invention, and the present invention is not limited to these. Among them, the embodiment (1), that is, a laminated structure of (laminate layer) / (intermediate layer) / (resin layer (B)) / (seal layer (A)), is preferred.

[0079] The multilayer film of the present invention can realize excellent antifogging properties, and can realize suitable seal strength when heat sealed, and can maintain suitable easy-opening properties between the seal layer (A) and the resin layer (B) used in the present invention when opened. In addition, the antifogging agent is unlikely to fall off, and the antifogging properties can be stably maintained, and the adhesion to printing and other substrates is also good.

[0080] The total thickness of the multilayer film of the present invention is preferably 20 μm or more because film formation is easy, and the total thickness is preferably 100 μm or less, particularly preferably 50 μm or less, because lamination is easy when the multilayer film of the present invention is used by laminating it with another substrate.

[0081] In addition, from the viewpoints of sealability, ease of opening, and lamination, it is preferable that the thickness ratio of the laminate layer in the multilayer film is in the range of 20 to 85%, the thickness ratio of the resin layer (B) is in the range of 10 to 40%, and the thickness ratio of the seal layer (A) is in the range of 5 to 20%.

[0082] The total amount of the antifogging agent contained in the entire antifogging multilayer film of the present invention is preferably 0.1% by mass or more based on the total mass of the film. When the total amount of the antifogging agent is within this range, suitable antifogging properties and durability of antifogging properties can be obtained. In addition, the upper limit of the total amount of the antifogging agent is preferably 0.7% by mass or less based on the total mass of the film, and particularly preferably 0.5% by mass or less. When the total amount of the antifogging agent is within this range, the film cutability is good and deterioration of the seal strength over time is easily suppressed.

[0083] In the multilayer film of the present invention, the surface on the laminate layer side is preferably treated to a wetting tension in the range of 35 to 45 mN / m. Examples of such a treatment method include surface oxidation treatments such as corona discharge treatment, plasma treatment, chromic acid treatment, flame treatment, hot air treatment, ozone / ultraviolet treatment, and surface roughening treatments such as sandblasting, and preferably corona discharge treatment. By carrying out such a surface treatment, when a post-process such as printing or applying an adhesive to the surface on the polyolefin resin layer side of the multilayer film is carried out, the coatability of ink or adhesive becomes good, and the adhesion to ink, aluminum, anchor coating agent, etc. is excellent, and problems such as falling off of ink or evaporated aluminum and delamination can be easily avoided.

[0084] In the multilayer film of the present invention, it is also preferable that the surface on the sealing layer (A) side is treated to have a wet tension in the range of 50 to 60 mN / m. By treating the surface on the sealing layer (A) side, it becomes possible to fix the antifogging agent to the surface for a relatively long period of time, resulting in a film with excellent antifogging properties and antifogging durability. The treatment method and the treatment extent of the polyolefin resin layer side surface and the seal layer (A) side surface may be the same or different, but from the viewpoint of productivity, it is preferable to treat them by the same method.

[0085] (Manufacturing method) The method for producing the multilayer film of the present invention is not particularly limited, but examples thereof include a coextrusion method in which each resin or resin mixture used for each layer is heated and melted in a separate extruder, laminated in the molten state in the order of the layer structure of the present invention by a method such as a coextrusion multilayer die method or a feed block method, and then formed into a film by an inflation method, a T-die chill roll method, or the like. This coextrusion method is preferable because it allows relatively free adjustment of the thickness ratio of each layer, and a multilayer film with excellent hygiene and cost performance can be obtained. Among them, the T-die chill roll method is preferable because it is easy to suppress deterioration of the film appearance when resins with different melting points or Tg are coextruded, and it is easy to form a uniform layer structure, and it is easy to obtain a multilayer film with suitable transparency and gloss. In addition, the inflation method is preferable because the equipment is simple and it is also suitable for small-scale production of a wide variety of products.

[0086] The multilayer film of the present invention can be obtained as a substantially unstretched multilayer film by the above-mentioned production method, and therefore can be subjected to secondary forming such as deep drawing by vacuum forming or embossing.

[0087] Immediately after extrusion of the laminate layer or the seal layer, the laminate layer or the seal layer may be embossed by contacting it with a roll having projections and recesses.

[0088] (Laminate) The multilayer film of the present invention can be laminated, for example by bonding with a substrate, to form a laminate. The laminate of the present invention may have the following structure: (1) Substrate / Adhesive Layer / Multilayer Film of the Present Invention (2) Substrate / adhesive layer / printed layer / multilayer film of the present invention (3) Substrate / adhesive layer / second substrate / printed layer / adhesive layer / multilayer film of the present invention (4) Substrate / adhesive layer / first printed layer / second printed layer / multilayer film of the present invention (5) Substrate / adhesive layer / barrier layer / adhesive layer / multilayer film of the present invention (6) Substrate / adhesive layer / barrier layer / printed layer / adhesive layer / multilayer film of the present invention (7) Substrate / printed layer / adhesive layer / multilayer film of the present invention (8) Substrate / first printed layer / second printed layer / adhesive layer / multilayer film of the present invention (9) Substrate / printing layer / adhesive layer / barrier layer / adhesive layer / multilayer film of the present invention and the like, but are not limited thereto, and may further include an additional substrate. The second and additional substrates may be unstretched resin films, stretched resin films, metal-vapor-deposited films such as metal-vapor-deposited unstretched films and metal-vapor-deposited stretched films, transparent vapor-deposited films, or papers such as coated paper and fine paper, and are not particularly limited. Furthermore, the multiple adhesive layers may have the same composition or different compositions. Furthermore, in order to improve the adhesive strength of the adhesive layer, an anchor coat layer may be sandwiched between the layers.

[0089] The method for laminating the multilayer film of the present invention and the base film is not particularly limited, and any combination technique such as dry lamination, wet lamination, non-solvent lamination, extrusion lamination, sand lamination, and thermal lamination may be used.

[0090] Examples of the stretched resin film include biaxially oriented polyester (PET), easily tearable biaxially oriented polyester (PET), biaxially oriented polypropylene (OPP), biaxially oriented polyamide (PA), coextruded biaxially oriented polypropylene with an ethylene-vinyl alcohol copolymer (EVOH) as the central layer, biaxially oriented ethylene-vinyl alcohol copolymer (EVOH), and coextruded biaxially oriented polypropylene coated with polyvinylidene chloride (PVDC). Among these, a film made of an α-olefin resin is preferably used, and it is particularly preferable to use a polypropylene resin film such as biaxially oriented polypropylene (OPP). Furthermore, the plastic film may be coated with a coating for the purpose of improving gas barrier properties or ink receptivity when a printing layer is provided, as described below. Commercially available coated plastic films include K-OPP film and K-PET film. These may be used alone or in combination.

[0091] The thickness of the stretched resin film is preferably from 10 to 60 μm, more preferably from 20 to 40 μm, and further preferably from 20 to 30 μm. When the thickness of the stretched resin film is within this range, production of a laminate film becomes easy.

[0092] Examples of the unstretched resin film include a CPP film, a nylon film, a PET film, and a PVC film. Combinations of two or more substrates may also be used.

[0093] The substrate may be made of a biomass polyolefin. The biomass polyolefin refers to a polyolefin resin that uses plant-derived olefin as a raw material monomer. The raw material monomer may contain petroleum-derived monomers, and does not have to contain 100% plant-derived monomers. As the biomass polyolefin, commercially available products can also be used. Examples of commercially available products include SGM9450F, SLL118, SLL118 / 21, SLL218, SLL318, SLH118, SLH218, and SLH0820 manufactured by Braskem.

[0094] The substrate to be laminated on the multilayer film of the present invention may be a substrate having a vapor-deposited layer made of an inorganic substance and / or an inorganic oxide provided on the above-mentioned resin film. By using a substrate provided with such a vapor deposition layer, it is possible to impart barrier properties to the laminate of the present invention. The deposition layer can be formed by a known method using a known inorganic substance or inorganic oxide, and the composition and the method of formation are not particularly limited. Furthermore, the laminate film made of the multilayer film of the present invention may have two or more vapor-deposited layers, which may have the same composition or different compositions.

[0095] The vapor-deposited layer may be, for example, a vapor-deposited film of an inorganic substance or an inorganic oxide such as silicon (Si), aluminum (Al), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), or yttrium (Y). Moreover, a vapor-deposited film of an inorganic oxide such as silicon oxide or aluminum oxide is transparent.

[0096] The inorganic oxides are expressed as MOx (wherein M represents an inorganic element), such as SiOx and AlOx. The value of x can range from 0-2 for silicon (Si), 0-1.5 for aluminum (Al), 0-1 for magnesium (Mg), 0-1 for calcium (Ca), 0-0.5 for potassium (K), 0-2 for tin (Sn), 0-0.5 for sodium (Na), 0-1.5 for boron (B), 0-2 for titanium (Ti), 0-1 for lead (Pb), 0-2 for zirconium (Zr), and 0-1.5 for yttrium (Y). In the above, when x=0, it is a completely inorganic element (pure substance) and is not transparent, and when the value of x is at the upper limit of the range, it indicates that it is completely oxidized. Silicon (Si) or aluminum (Al) is preferably used for the vapor deposition layer, and silicon (Si) with an x ​​value in the range of 1.0 to 2.0 and aluminum (Al) with an x ​​value in the range of 0.5 to 1.5 can be used.

[0097] The deposition layer can be formed on the surface of the substrate by a method such as a physical vapor deposition method (PVD method) including a vacuum deposition method, a sputtering method, and an ion plating method, or a chemical vapor deposition method (CVD method) including a plasma chemical vapor deposition method, a thermal chemical vapor deposition method, and a photochemical vapor deposition method.

[0098] The thickness of the vapor-deposited layer is not particularly limited as long as the vapor-deposited layer alone can exhibit a certain level of gas barrier function. The preferred range of thickness varies depending on the type of metal or metal oxide to be deposited, but is preferably 0.05 to 70 nm, more preferably 0.1 to 70 nm, even more preferably 3 to 70 nm, and even more preferably 5 to 60 nm.

[0099] As the metal-deposited film, a VM-CPP film in which a metal such as aluminum is deposited on a CPP film, or a VM-OPP film in which a metal such as aluminum is deposited on an OPP film can be used. Examples of the transparent vapor-deposited film include films obtained by depositing silica or alumina on OPP films, PET films, nylon films, and the like. For the purpose of protecting the inorganic vapor deposition layer of silica or alumina, a film having a coating applied onto the vapor deposition layer may be used.

[0100] In addition, for applications that do not require transparency, aluminum foil can be used alone or in combination as a barrier layer, but since the multilayer film of the present invention has excellent anti-fogging properties, it is preferable not to use aluminum foil as a barrier layer in order to exhibit the anti-fogging properties.

[0101] Paper may also be used as the substrate. For example, paperboard such as coated cardboard, card paper, ivory paper, and manila cardboard used for printing on packaging materials and packages for cosmetics, beverages, medicines, toys, and equipment, milk carton base paper, cup base paper, fine paper, craft paper, pure white roll paper, glassine paper, parchment paper, manila cardboard, white cardboard, coated paper, art paper, imitation paper, thin paper, thick paper, polyethylene coated paper, various synthetic papers, acid-resistant paper, etc. can be used.

[0102] Examples of the lamination method for laminating the above-mentioned substrate or a substrate subjected to printing or deposition onto the multilayer film of the present invention to form a laminate include dry lamination, wet lamination, non-solvent lamination, extrusion lamination, and the like. In this case, the layer located between the sealant film and the substrate is called an adhesive layer.

[0103] The adhesive used in the dry lamination may be, for example, a solvent-based two-liquid curing adhesive. A "solvent-based" adhesive refers to a form used in a method in which the adhesive is applied to a substrate, heated in an oven or the like to volatilize the organic solvent in the coating, and then bonded to another substrate, a so-called dry lamination method, and contains a polyisocyanate composition, a polyol composition, and an organic solvent capable of dissolving (diluting) them.

[0104] In the above two-component curing adhesive, in consideration of the creation of a recycling-based society that should develop in a sustainable manner (sustainability), it is preferable to use plant-derived raw materials (biomass raw materials) as raw materials for the polyisocyanate composition or polyol composition. By using biomass raw materials appropriately, the environmental burden can be reduced. Examples of biomass raw materials include castor oil-based polyols such as castor oil, dehydrated castor oil, hydrogenated castor oil, and 5 to 50 mole alkylene oxide adducts of castor oil; aliphatic polybasic acids such as succinic acid, succinic anhydride, glutaric acid, adipic acid, azelaic acid, sebacic acid, and itaconic acid; alkyl esters of these acids; and dimer acids.

[0105] As the adhesive using biomass raw materials, commercially available products can also be used. As commercially available products, adhesives and the like listed in the Japan Organics Resources Association can be used, such as DIC Dry BM (manufactured by DIC Corporation) and Takenate BM (Mitsui Chemicals, Inc.).

[0106] The weight of the adhesive layer after drying is 0.1 to 10 g / m 2 is preferably 1 to 6 g / m 2 More preferably, the thickness is 2 to 5 g / m 2 It is even more preferable that: The thickness of the adhesive layer is preferably 0.1 to 10 μm, more preferably 1 to 7 μm, and even more preferably 2 to 5 μm.

[0107] Although various adhesives can be used for the adhesive layer, it is preferable to use a pressure-sensitive adhesive. Examples of the pressure-sensitive adhesive include rubber-based adhesives obtained by dissolving polyisobutylene rubber, butyl rubber, or mixtures thereof in organic solvents such as benzene, toluene, xylene, or hexane; or these rubber-based adhesives blended with tackifiers such as abiethylene acid rosin ester, terpene-phenol copolymer, or terpene-indene copolymer; and acrylic-based adhesives obtained by dissolving acrylic copolymers with a glass transition temperature of -20°C or lower, such as 2-ethylhexyl acrylate-n-butyl acrylate copolymer or 2-ethylhexyl acrylate-ethyl acrylate-methyl methacrylate copolymer, in an organic solvent.

[0108] When a material having gas barrier properties is used as the above adhesive or the anchor coating agent described below, a laminate film having particularly excellent barrier properties can be obtained. As an adhesive with excellent gas barrier properties, 3 g / m 2 The oxygen barrier property of the cured coating of the adhesive applied at (solid content) is 300cc / m 2 / day / atm or less, or water vapor barrier property of 120g / m 2 / day means that at least one of the following conditions is satisfied. Commercially available products include the "PASLIM" series, such as PASLIM VM001 and PASLIM J350X manufactured by DIC Corporation, and "Maxive" manufactured by Mitsubishi Gas Chemical Company.

[0109] The adhesive layer can also be formed from a thermoplastic resin, and the method for forming the adhesive layer can be a conventional method such as a melt extrusion lamination method or a sand lamination method. Examples of the thermoplastic resin that can be used for the adhesive layer include polyethylene-based resins such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), and high-density polyethylene (HDPE); polypropylene-based resins such as propylene homopolymers, propylene-α-olefin random copolymers, and propylene-α-olefin block copolymers; norbornene-based polymers and hydrogenated products thereof, such as norbornene-based copolymers (COC) obtained by copolymerizing norbornene-based monomers with olefins such as ethylene; vinyl alicyclic hydrocarbon polymers; and cyclic polyolefin-based resins such as cyclic conjugated diene polymers; Examples of the elastomer include polyethylene-based elastomers such as ethylene-vinyl acetate copolymer (EVA) and ethylene-α-olefin copolymer, polypropylene-based elastomers, butene-based elastomers, etc.; ethylene-based copolymers such as ethylene-methyl methacrylate copolymer (EMMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl acrylate (EMA) copolymer, ethylene-ethyl acrylate-maleic anhydride copolymer (E-EA-MAH), ethylene-acrylic acid copolymer (EAA), and ethylene-methacrylic acid copolymer (EMAA); and further examples include ionomers of ethylene-acrylic acid copolymers and ionomers of ethylene-methacrylic acid copolymers. In order to improve the adhesion between layers, it is also possible to use acid-modified polyolefin resins obtained by modifying the above-mentioned polyolefin resins with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, and itaconic acid. In addition, resins obtained by graft polymerizing or copolymerizing an unsaturated carboxylic acid, an unsaturated carboxylic anhydride, or an ester monomer with a polyolefin resin can also be used. These resins may be used alone or in combination of two or more. It is also preferable to use, as the polyethylene-based resin, one that uses ethylene derived from biomass as a monomer unit.

[0110] When the adhesive layer is laminated by extrusion lamination, an anchor coat layer may be provided on the surface of the layer to be laminated by applying and drying an anchor coat agent. Examples of anchor coating agents include anchor coating agents made of any resin with a heat resistance temperature of 135°C or higher, such as polybutadiene resins, urethane resins, polyisocyanate-polyether polyols, polyethyleneimines, vinyl modified resins, epoxy resins, polyester resins, alkyl titanates, etc., as well as anchor coating agents obtained by diluting the above adhesives with organic solvents. Among these, polyethyleneimine-based anchor coating agents and anchor coating agents obtained by diluting the above adhesives with an organic solvent are preferably used. A silane coupling agent may be used in combination with this as an additive, and soluble nitrocellulose may be used in combination to enhance heat resistance.

[0111] When the laminate of the present invention is obtained by laminating the multilayer film of the present invention and a substrate or the like by an extrusion lamination method or a sand lamination method, the nip roll or chill roll used during lamination may be an embossing roll to apply embossing to the surface on the seal layer side.

[0112] The laminate of the present invention may further include a printed layer between the multilayer film of the present invention and the above-mentioned substrate. The printing layer is a layer on which a desired pattern is formed using liquid printing ink in order to impart aesthetic appeal, various information regarding the contents, and functionality to the printed material. The printing layer is formed by printing a gravure printing ink or flexographic printing ink (hereinafter referred to as liquid printing ink) containing a binder resin and a colorant, an active energy ray curable ink, or an inkjet ink. The printed layer may be a single layer, or there may be multiple printed layers. When there are multiple printed layers, the liquid printing ink used for each printed layer may be the same, may be the same composition but with different colorants, or may be of different compositions. Also, printing may be performed using two types of printing inks in combination, such as liquid printing ink and inkjet ink. In the case where there are multiple printed layers, the printed matter may have, for example, a first printed layer formed from a printing ink containing a colorant, a second white printed layer formed from a liquid ink containing a white pigment as a colorant, and a third white printed layer, in that order. The first printed layer can form a picture using a colorant, and the second white printed layer formed with a liquid ink containing a white pigment, and the third printed layer can be used as a background for the picture. When the second or third printed layer is an overprint varnish, it does not need to contain a colorant.

[0113] The liquid printing inks are used as gravure printing inks or flexographic printing inks, and are roughly divided into organic solvent-based liquid printing inks that use an organic solvent as the main solvent, and water-based liquid printing inks that use water as the main solvent. The printing layer is preferably a general-purpose organic solvent-based liquid printing ink.

[0114] The organic solvent-based liquid printing ink is prepared by dispersing a mixture of a pigment, a binder resin, an organic solvent medium, a dispersant, an antifoaming agent, etc., in a dispersing machine to obtain a pigment dispersion. To the obtained pigment dispersion, a resin, an aqueous medium, and, if necessary, additives such as a leveling agent are added, and the mixture is stirred to obtain the dispersion. The dispersion may be carried out using a bead mill, Eiger mill, sand mill, gamma mill, attritor or the like that is generally used in the manufacture of gravure and flexographic printing inks.

[0115] Examples of the binder resin include cellulose-based resins such as cellulose-based resins such as nitrocellulose, cellulose acetate propionate (CAP) and cellulose acetate butyronate (CAB), polyamide-based resins, polyurethane resins, acrylic resins, vinyl chloride-vinyl acetate copolymer resins, chlorinated polypropylene resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, polyvinyl chloride resins, vinyl chloride-acrylic copolymer resins, and other vinyl chloride resins, polyester resins, alkyd resins, rosin-based resins, rosin-modified maleic acid resins, ketone resins, cyclized rubber, chlorinated rubber, butyral, and petroleum resins. Among these, polyurethane resins are preferably used.

[0116] The polyurethane resin is preferably a polyurethane resin obtained by polymerizing a polyol and a polyisocyanate. The polyol is preferably a polyester polyol. If necessary, the polyurethane resin may be synthesized by using in combination a general-purpose polyol other than the polyether polyol, the polyester polyol, and the polyether polyol, a chain extender, a terminal blocking agent, and the like. Furthermore, the polyol may be reacted with a polyisocyanate to form a urethane prepolymer having an isocyanate group at its terminal, and the urethane prepolymer may be reacted with a polyamine compound to synthesize a polyurethane resin. The polyurethane resin may be used alone or in combination in the liquid ink.

[0117] Examples of the pigment include inorganic pigments and organic pigments that are commonly used in inks, paints, recording materials, and the like. Examples of the organic pigment include soluble azo-based, insoluble azo-based, azo-based, phthalocyanine-based, halogenated phthalocyanine-based, anthraquinone-based, anthanthrone-based, dianthraquinonyl-based, anthrapyrimidine-based, perylene-based, perinone-based, quinacridone-based, thioindigo-based, dioxazine-based, isoindolinone-based, quinophthalone-based, azomethine azo-based, flavanthrone-based, diketopyrrolopyrrole-based, isoindoline-based, indanthrone-based, and carbon black-based pigments. Further examples include carmine 6B, lake red C, permanent red 2B, disazo yellow, pyrazolone orange, carmine FB, chromophthalic yellow, chromophthalic red, phthalocyanine blue, phthalocyanine green, dioxazine violet, quinacridone magenta, quinacridone red, indanthrone blue, pyrimidine yellow, thioindigo bordeaux, thioindigo magenta, perylene red, perinone orange, isoindolinone yellow, aniline black, diketopyrrolopyrrole red, and daylight fluorescent pigments. In addition, either a non-acid-treated pigment or an acid-treated pigment can be used.

[0118] Examples of the inorganic pigment include white inorganic pigments such as titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silica, lithopone, antimony white, and gypsum. Among the inorganic pigments, titanium oxide is particularly preferred. Titanium oxide is white in color and is preferred from the standpoints of coloring power, hiding power, chemical resistance, and weather resistance, and from the standpoint of printing performance, the titanium oxide is preferably treated with silica and / or alumina. Examples of inorganic pigments other than white include aluminum particles, mica, bronze powder, chrome vermilion, yellow lead, cadmium yellow, cadmium red, ultramarine, Prussian blue, red iron oxide, yellow iron oxide, and zircon. Aluminum is in powder or paste form, but it is preferable to use it in paste form from the standpoint of handleability and safety. Whether leafing or non-leafing aluminum is used is appropriately selected from the standpoint of brightness and concentration.

[0119] The organic solvent is not particularly limited, and examples thereof include aromatic hydrocarbon organic solvents such as toluene, xylene, Solvesso #100, Solvesso #150, etc.; aliphatic hydrocarbon organic solvents such as hexane, methylcyclohexane, heptane, octane, decane, etc.; and various ester-based organic solvents such as methyl acetate, ethyl acetate, isopropyl acetate, normal propyl acetate, butyl acetate, amyl acetate, ethyl formate, butyl propionate, etc. Examples of water-miscible organic solvents include various organic solvents such as alcohols, such as methanol, ethanol, propanol, butanol, and isopropyl alcohol; ketones, such as acetone, methyl ethyl ketone, and cyclohexanone; and glycol ethers, such as ethylene glycol (mono, di)methyl ether, ethylene glycol (mono, di)ethyl ether, ethylene glycol monopropyl ether, ethylene glycol monoisopropyl ether, monobutyl ether, diethylene glycol (mono, di)methyl ether, diethylene glycol (mono, di)ethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monobutyl ether, triethylene glycol (mono, di)methyl ether, propylene glycol (mono, di)methyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, and dipropylene glycol (mono, di)methyl ether. These may be used alone or in combination of two or more.

[0120] From the viewpoints of work hygiene during printing and the harmfulness of packaging materials, it is more preferable to use ethyl acetate, propyl acetate, isopropanol, normal propanol, etc., and not to use aromatic solvents such as toluene or ketone solvents such as methyl ethyl ketone. Among these, from the viewpoint of the solubility of the polyurethane resin, a mixed liquid of isopropyl alcohol / ethyl acetate / methoxypropanol is more preferable. Furthermore, glycol ethers can be added in an amount of less than 10% by mass of the total ink to adjust the drying rate.

[0121] The organic solvent-based liquid printing ink has excellent adhesion to various substrates and can be used for printing on paper, synthetic paper, thermoplastic resin films, plastic products, steel plates, etc., and is useful as an ink for gravure printing using a gravure printing plate made by electronic engraving or the like, or for flexographic printing using a flexographic printing plate made by a resin plate or the like. The film thickness of the liquid printing ink formed by gravure printing or flexographic printing using the organic solvent-based liquid printing ink is preferably 0.1 to 10 μm, more preferably 1 to 5 μm, and even more preferably 1 to 3 μm. The weight of the printed layer after drying is 0.1 to 10 g / m 2 is preferably 1 to 5 g / m 2 More preferably, it is 1 to 3 g / m 2 It is even more preferable that:

[0122] In the above liquid printing ink, in consideration of the establishment of a recycling-based society that should develop in a sustainable manner (sustainability), it is preferable to use a liquid printing ink that uses raw materials derived from plants (biomass raw materials). Examples of plant-derived raw materials include cellulose resins such as cellulose acetate propionate resin and nitrocellulose; polyamide resins using dimer acids or polymerized fatty acids derived from natural oils such as soybean oil, palm oil, and rice bran oil; polycarboxylic acids such as succinic acid, succinic anhydride, adipic acid, azelaic acid, sebacic acid, dimer acid, glutaric acid, and malic acid; polyols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, pentylene glycol, 1,10-dodecanediol, dimer diol, and isosorbide; and polyisocyanates such as 1,5-pentamethylene diisocyanate and dimer diisocyanate. These polycarboxylic acids include biomass polyurethanes synthesized from plant-derived raw materials, rosin resins, dammar resins, and polylactic acid.

[0123] As the liquid printing ink using the above-mentioned plant-derived raw materials, commercially available products can also be used. As commercially available products, inks and the like listed in the Japan Organics Resources Association (general incorporated association) can be used, such as Finart BM (manufactured by DIC Corporation), LP Bio Series (manufactured by Toyo Ink Co., Ltd.), Bellflora (manufactured by Sakata Inx Corporation), and NB300 BP Series (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.).

[0124] The above-mentioned printed layer may be printed on another substrate by so-called reverse printing, and then the substrate and the multilayer film of the present invention may be laminated by a method such as dry lamination, sand lamination, extrusion lamination, etc. The extrusion lamination method is preferable because it reduces the production load since it is possible to carry out the production of the multilayer film of the present invention, lamination with the substrate, and, in some cases, embossing of the seal layer of the multilayer film in a single process. Additionally, an anchor coat varnish, an overcoat varnish, or the like may be used.

[0125] <Packaging material> The use of the multilayer film or laminate of the present invention is not particularly limited, but it can be used as a packaging material for food, medicine, industrial parts, miscellaneous goods, magazines, etc., and can be particularly suitably used as a lid material for packaging containers. In particular, it is preferable that the outermost layer of the packaging container (the part that adheres to the seal layer (A) of the multilayer film of the present invention) contains a polyester-based resin from the viewpoint of the balance between easy opening and seal strength. In addition, since it exhibits excellent anti-fogging properties, it can be suitably used for packaging foods that contain a lot of moisture, and is preferably used as a lid material for food packaging containers.

[0126] The packaging bag is preferably a packaging bag formed by overlapping and sealing the sealing layers of the multilayer film or laminate of the present invention, or overlapping and sealing the outermost layer and the sealing layer. For example, two sheets of the multilayer film are cut to the desired size of the packaging bag, overlapped and sealed at three sides to form a bag, and then the contents are filled in from the unsealed side and sealed to form a packaging bag. Furthermore, it is also possible to form a packaging bag by sealing the ends of a rolled film into a cylindrical shape using an automatic packaging machine, and then sealing the top and bottom.

[0127] The multilayer film or laminate of the present invention can also be used to form a packaging bag or container by overlapping and sealing another sealable film with the sealing layer (A). In this case, a film having a relatively low mechanical strength such as LDPE or EVA can be used as the other film. A laminate film obtained by bonding a film such as LDPE or EVA with a stretched film having a relatively good tearability, such as a biaxially oriented polyethylene terephthalate film (OPET) or a biaxially oriented polypropylene film (OPP), can also be used.

[0128] (Sealing method) The multilayer film or laminate of the present invention has a sealability and can be used to form a package by sealing. The seal strength of the multilayer film or laminate of the present invention may be adjusted appropriately depending on the mode of use. For example, the multilayer film or laminate of the present invention is heat-sealed to an A-PET sheet (softening point 77°C, crystallization temperature 126°C) at a temperature of 140°C and a pressure of 0.2 MPa for 1.0 second, and then a test piece having a width of 15 mm is cut out and peeled in a 180° direction at a tensile speed of 300 mm / min in a thermostatic chamber at 23°C and 50% RH. The maximum load is preferably 3N / 15mm or more, more preferably 5N / 15mm or more, and even more preferably 6N / 15mm or more. The upper limit of the maximum load is preferably less than 20N / 15mm, and more preferably less than 15N / 15mm. By setting the peel strength to this value, the multilayer film is less likely to peel or fall off, and is particularly suitable for easy opening when opened. In addition to heat sealing, ultrasonic sealing can also be applied to the multilayer film of the present invention. The method of ultrasonic sealing is not particularly limited, and a known ultrasonic sealing method or a method using a known ultrasonic sealing device can be appropriately selected depending on the purpose.

[0129] In packaging materials using the multilayer film or laminate of the present invention, it is preferable to form any tear initiation portion such as a V notch, an I notch, a perforation, or a microhole in the sealed portion in order to weaken the initial tear strength and improve the ease of opening. EXAMPLES

[0130] The present invention will now be described in more detail with reference to examples and comparative examples. In the following, unless otherwise specified, "parts" are by mass.

[0131] <Polyester resin> The composition of the polyester resin used is shown below. Polyester 1: terephthalic acid / isophthalic acid / ethylene glycol = 30 / 10 / 40 (molar ratio) [glass transition temperature: 72°C] Polyester 2: terephthalic acid / ethylene glycol / 1,4-cyclohexanedimethanol / isosorbide = 50 / 20 / 27.5 / 2.5 (molar ratio) [glass transition temperature: 90°C] Polyester 3: terephthalic acid / adipic acid / 1,4-butanediol = 24.5 / 25.5 / 50 (molar ratio) [glass transition temperature: -35°C, melting point: 120°C] Polyester 4: terephthalic acid / isophthalic acid / polytetramethylene ether glycol / 1,4 butanediol = 33.3 / 16.7 / 33.3 / 16.7 [glass transition temperature: -70°C, melting point: 127°C] Polyester 5: Terephthalic acid / 1,4 butanediol / polytetramethylene ether glycol = 50 / 35 / 15 [glass transition temperature: -32°C, melting point: 165°C]

[0132] <Preparation of anti-fog agent masterbatch based on polyester resin> (Preparation Example 1) [Preparation of anti-fog masterbatch based on polyester 1] 90 parts of polyester 1 and 10 parts of a nonionic surfactant (diglycerol fatty acid ester, HLB: 6) were melt-kneaded and granulated to obtain anti-fogging agent master batch pellets (hereinafter referred to as anti-fogging agent MB1).

[0133] (Preparation Example 2) [Preparation of anti-fog masterbatch based on polyester 2] 90 parts of polyester 2 and 10 parts of a nonionic surfactant (diglycerol fatty acid ester, HLB: 6) were melt-kneaded and granulated to obtain anti-fogging agent master batch pellets (hereinafter referred to as anti-fogging agent MB2).

[0134] (Preparation Example 3) [Preparation of anti-fog masterbatch based on polyester 5] 90 parts of Polyester 5 and 10 parts of a nonionic surfactant (diglycerol fatty acid ester, HLB: 6) were melt-kneaded and granulated to obtain anti-fogging agent master batch pellets (hereinafter referred to as anti-fogging agent MB3).

[0135] Example 1 For the sealing layer (A), a mixture of polyester 1, polyester 3, and anti-fog agent MB1 was used in a ratio of polyester 1 / polyester 3 / nonionic surfactant=48 parts / 48.5 parts / 3.5 parts. Linear low-density polyethylene (density 0.93 g / cm) was used as the lamination layer. 3 , melt flow rate 6g / 10min (230℃); hereinafter referred to as LLDPE) was used. LLDPE is used as the middle layer, Resin layer (B) is an acid-modified ethylene-propylene-butene copolymer (acid modification amount 2.9 parts by mass, density 0.89 g / cm 3 (hereinafter referred to as adhesive resin) Resins were supplied to each of the extruder for the seal layer (A) (diameter 40 mm), the extruder for the resin layer (B) (diameter 40 mm), the extruder for the intermediate layer (diameter 50 mm), and the extruder for the laminate layer (diameter 50 mm), and by co-extrusion, the laminate layer / intermediate layer / resin layer (B) / seal layer (A) were extruded from a T-die at an extrusion temperature of 230°C so that the thicknesses of the laminate layer / intermediate layer / resin layer (B) / seal layer (A) were 9 μm / 12 μm / 6 μm / 3 μm, and the films were cooled with a water-cooled metal cooling roll at 30°C and subjected to corona discharge treatment so that the wet tension of the laminate layer was 40 mN / m.The films were then wound up on a roll and aged for 36 hours in an aging chamber at 40°C to obtain a multilayer film of Example 1 having a total thickness of 30 μm.

[0136] (Examples 2 to 8) The films of Examples 2 to 7 were produced in the same manner as in Example 1, except that the compositions shown in the table were used.

[0137] Example 9 For the sealing layer (A), a mixture of an antiblocking agent (CAS number: 1344-01-0), polyester 1, polyester 3, and antifogging agent MB1 was used in a ratio of polyester 1 / polyester 3 / nonionic surfactant / antiblocking agent = 65.5 parts / 30 parts / 3.5 parts / 1 part. The film of Example 9 was produced in the same manner as in Example 1, except that a polyethylene-based antifogging agent MB (ESR-702 manufactured by Riken Vitamin Co., Ltd.) was used as the laminate layer, silica (CAS number: 7631-86-9) was used as the antiblocking agent, and a mixture of LLDPE / antifogging agent / antiblocking agent=98.5 parts / 0.5 parts / 1 part was used.

[0138] Example 10 A film of Example 10 was produced in the same manner as in Example 1, except that the composition in the table was used.

[0139] (Comparative Examples 1 to 7) Films of Comparative Examples 1 to 7 were produced in the same manner as in Example 1, except that the compositions shown in the table were used.

[0140] (Evaluation of anti-fogging properties) A biaxially stretched polyester film with a thickness of 12 μm was laminated to the polyolefin resin layer side of the obtained multi-layer film using a dry lamination adhesive to prepare a laminate film. In this case, a two-component curing adhesive (polyester adhesive "LX500" and curing agent "KW-75") manufactured by DIC Corporation was used as the dry lamination adhesive. The film was made of A-PET, had a 5 mm wide, smooth surface, a square shape with a side length of 88 mm, and a capacity of 80 cm. 3 30 ml of water at 40°C was poured into the container, and the sealing layer (A) side of the obtained laminate film was placed on the container and heat-sealed using a cup sealer. The film was then stored at 3°C, and the anti-fog effect was visually confirmed after 1 hour and 3 hours according to the following criteria. (Anti-Fog Evaluation Criteria) ◎: A continuous water film was formed on the film surface after 1 hour, and visibility was good. 〇: A continuous water film was formed on the film surface after 3 hours, and visibility was good. ×: Water droplets attached, visibility deteriorated

[0141] (Method of evaluating peeling surface (film tearability) after cup sealing) A peel test was carried out on the A-PET containers for which the anti-fogging properties were measured, with the peel angle fixed at 45° using a 45° peel test fixture (manufactured by Imada Co., Ltd.) The appearance of the containers after peeling was visually inspected and evaluated according to the following criteria. (Membrane tearability evaluation criteria) ◎: No film remains even when opened at 30 mm / min. ○: No film residue is left even when opened at 100 mm / min. △: No film residue was observed even when opened at 250 mm / min. ×: Film residue of the sealing layer (A) occurred.

[0142] (Evaluation of heat sealability) The sealing layer (A) side of the laminate film was placed on an A-PET sheet (softening point 77°C, crystallization temperature 126°C), and heat sealed for 1.0 second with a 10mm wide seal bar at a temperature of 140°C and a pressure of 0.2MPa using a precision heat sealer (manufactured by Tester Sangyo). The sample was then allowed to cool, and a 15mm wide test piece was cut out from the heat-sealed sample. The maximum load was measured by peeling it off in a 180° direction using a universal tensile tester (manufactured by A&D Co., Ltd.) at a tensile speed of 300mm / min in a thermostatic room at 23°C and 50% RH (unit: N / 15mm). (Heat sealability evaluation criteria) 〇: 6N or more / 15mm △: 4~6N / 15mm ×: 4N or less / 15mm

[0143] (Hayes's rating) The haze of the multilayer films of the examples and comparative examples was measured using a haze meter (manufactured by Nippon Denshoku Kogyo Co., Ltd.) based on JIS K 7105:1981. ◎: 8% or less 〇: 8~15% ×: 15% or more

[0144] [Table 1]

[0145] [Table 2]

[0146] As is clear from the above table, the multilayer films of the present invention in Examples 1 to 10 were able to achieve suitable anti-fogging properties, film tearability, and heat seal strength. On the other hand, the multilayer films of Comparative Examples 1 to 5, which did not contain a polyester resin in the resin layer (B), had relatively good anti-fogging properties, but had poor film cutability and low heat seal strength. The multilayer films of Comparative Examples 6 and 7, which did not contain an anti-fogging agent in the seal layer (A), also had poor anti-fogging properties.

Claims

1. The seal layer (A) and the resin layer (B) adjacent to the seal layer (A), The sealing layer (A) contains a polyester-based resin (a) and an antifogging agent, the resin layer (B) contains 40 to 95% by mass of an acid-modified polyolefin and a polyester-based resin (b); the amount of the antifogging agent in the sealing layer (A) is 1.0 to 5.0 masses based on the total mass of the sealing layer (A); The glass transition temperature of the polyester resin (b) is 45° C. or lower. Multilayer film.

2. The sealing layer contains a polyester-based resin (a1) and a polyester-based resin (a2) as polyester-based resins, The multilayer film according to claim 1, wherein the polyester resin (a1) has a glass transition temperature of 60 to 140° C., and the polyester resin (a2) has a glass transition temperature of 45° C. or lower.

3. The multilayer film according to claim 1, wherein a mass ratio of the acid-modified polyolefin to the polyester resin (b) in the resin layer (B) is 45:55 to 95:

5.

4. The multilayer film of claim 1 , further comprising a laminate layer (A).

5. A laminate comprising the multilayer film according to any one of claims 1 to 4.

6. A packaging material using the laminate according to claim 5.

7. The packaging material according to claim 6, which is a lid material for a food packaging container.

8. A food packaging container using the packaging material according to claim 7 as a lid material, wherein a portion of the food packaging container that is bonded to the lid material contains a polyester-based resin.

Citation Information

Patent Citations

  • Moisture-retarding, oxygen-blocking and flavor-retaining packaging film with anti-fog function

    CN103129832A

  • Easily opening co-extruded film, lid material and deep-drawn vessel using film

    JP2006281675A

  • multilayer sealant film

    JP2009543718A

  • Multilayer sealant film

    JP2013018549A

  • Extrudable anti-fog copolyester heat seal resin

    JP2020510708A